Emerging leadership practices in extremity: case study of women advancing collective enterprise in peace building processes, Riyom, Plateau State, Nigeria - Ari, Anisah (Kansas State University, 2024)
Nigeria has been dealing with protracted fratricidal and intractable communal conflicts, leaving its citizens dwelling in harsh deprivation, helplessness, and hopelessness in its wake. This is further exaggerated by poor leadership and economic insolvency, which has placed the country at a precipice of unprecedented poverty and insecurity. At the center of all this pathetic condition is poor leadership, which has affected provision of basic infrastructures like education, health, power, housing, water, sanitation, and hygiene. It also accounts for high levels of unemployment, with millions of idle minds available to mischief and notorious practices. The effect of poor or good leadership cannot be hidden, and this is manifested in the health of the ecosystem where it is occurring. This means that leadership is not static, it is dynamic, and its dynamism is locked in everyday practices. Several extant leadership literatures theorize that Nigeria is lacking in the exercise of leadership that meets the complexities and lived realities of our time. Leadership is not something you pick off the shelf and administer like a template or blueprint, and this has not served the country overtime. However, a crop of scholars and practitioners are evoking a practice turn, that elevates the need to look inwards, and be endogenously creative. These folks are engaging context driven consideration in approaching leadership, prioritizing cultural practices, the lived realities of the people, with cognizance of the ever-evolving face of peace and conflicts. This study sought to understand how context influences emergent local leadership practices in extremities. The research site is a conflict-ridden area which has experienced sporadic communal conflicts for over 23 years; highly patriarchal, with rigid gender and social hierarchy; and particularly under-resourced. This is a qualitative study, and leaned on the theoretical framework of adaptive leadership, leadership-as-practice, and everyday peace. A twining of constructivist approach and case study methodology was utilized to understand the phenomenon, through co-construction of meanings with the co-researchers. Eight women leading peace building engaged in this study, through in-depth semi-structured interviews using mediated mediums (Zoom and Phone calls). Data was analyzed using an abductive thematic analysis which surfaced eleven themes and compressed as three main themes: (1) Leadership requires authority(or authorizing self), inclusion and should be nimble; (2) Community groups working on peace building should consider communication, collaboration, supportive culture, and leading by example as essential practices; (3) Groups may be motivated to engage in peace building because of experiences of exclusion & marginalization, hardships & loss, the gendered impacts of conflicts, and empowerments from trainings. The synthesis of these themes informed the overarching theme that: Context has a mediating and moderating influence in the emergence and practice of peace leadership. The findings suggest that both intangible and tangible elements provide context to leadership. Leadership does not happen in a vacuum but requires a container that holds space for different elements to interact. The occupiers of this container serve as moderating or mediating factors that provokes progress of not. This includes the combination of the people (identities, reasoning) the culture and traditions (practice, artifacts), social norms, language, policies, and laws, lived experiences, and the environment. This study recommends that both peace leadership researchers and practitioners continue to expand the prism of theorizing and praxis to identify and center the varied and evolving elements within specific context as areas of inquiry. Finally, further research may consider how power structures (intergroup and intragroup) in extreme context are established, deconstructed, and dismantled in situatedness.
Emerging leadership practices in extremity: case study of women advancing collective enterprise in peace building processes, Plateau State, Nigeria
Keywords: Leadership; Community; Women agency; Indigenous; Peace building; Everyday practices